An Optimized Process for Expression, Scale-Up and Purification of Recombinant Erythropoietin Produced in Chinese Hamster Ovary Cell Culture - Surabattula, Rambabu; Sambasiva Rao, K.R.S.; Polavarapu, Ratnagiri (Research in Biotechnology, 2011)
The DHFR mediated gene amplification employed for selection of recombinant Chinese hamster ovary (rCHO) clones was evaluated by single and multiple step selection of methotrexate (MTX). Multiple step selection of MTX resulted in cells with high amplified copies of erythropoietin (EPO) gene. Expression of EPO rapidly increased with increasing MTX concentration up to 1000 nM, further increased to 2000 nM does not affect the expression. After the MTX selection, cells grown in the presence of MTX were more stable and retained similar amounts of EPO expression and gene copies until 50 doublings. Whereas, cells grown in the absence of MTX were unstable and retained only 50% of initial EPO expression and gene copies at the 50th doubling.